The silent claimant state: Brunei Darussalam in the South China Sea Region - Kurniati, Endah; Laksono, Dwi Putro Wibowo; Aulia, Jamal Din (Priviet Social Sciences Journal, 2025)
The South China Sea Areas of the sea have proven reserves of oil and gas and are a hot spot with high potential. However, it is the South China Sea’s weight as a geopolitical strain that sets it apart as a potential theater of conflict. It is a dispute between China, Indonesia, Taiwan, the Philippines (which had brought the case), Brunei Darussalam, Malaysia, and Vietnam due to overlapping territorial claims as well as China’s unilaterally drawing of the Nine-Dash Line. Brunei Darussalam is seen as a claimant state which does not make an overt claim to the Spratly Islands. Brunei Darussalam is also among the countries that have agreed on some of China’s projected cooperation schemes. China is a partner that can support Brunei, and it indirectly influences its political position by doing so, thus challenging ASEAN’s unified action on the South China Sea dispute.